2018
DOI: 10.1103/physrevmaterials.2.074601
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancies and hydrogen in amorphous In-Ga-Zn-O and ZnO

Abstract: Hydrogen is known to be present as an impurity in amorphous oxide semiconductors at the 0.1% level. The behavior of hydrogen and oxygen vacancies in amorphous In-Ga-Zn-O is studied using density functional supercell calculations. We show that the hydrogens pair up at oxygen vacancies in the amorphous network, where they form metal-H-metal bridge bonds. These bonds are shown to create filled defect gap states lying just above the valence band edge, infra-red modes at about 1400 and 1520 cm-1 , and they are show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 79 publications
4
32
0
Order By: Relevance
“…For other cases, the deep level always develops at weak bonding between metal atoms involving at least one In atom. Consistently, in previous calculations that analyzed the bonding environments around V O , it was revealed that the defect formation energy is lower when V O is surrounded by In atoms. Among the five models, defect levels are scattered over 1.7–2.1 eV from CBM.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…For other cases, the deep level always develops at weak bonding between metal atoms involving at least one In atom. Consistently, in previous calculations that analyzed the bonding environments around V O , it was revealed that the defect formation energy is lower when V O is surrounded by In atoms. Among the five models, defect levels are scattered over 1.7–2.1 eV from CBM.…”
Section: Resultssupporting
confidence: 84%
“…However, the conclusion on the nature of V O is sharply divided; while V O was found to be dominantly deep in Refs. , shallow property was also claimed in Refs. .…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Zn in ZnO has the d 10 s 0 electronic structure so that it also retains its high mobility in the amorphous (a-) phase. However ZnO is not easily made amorphous, with amorphisation of ZnO costing 0.4 eV per formula unit [15]. A second conductive oxide should be added to the ZnO to reduce the amorphization energy to be less than 0.15 eV/atom by the mixed alkali effect [15].…”
Section: Introductionmentioning
confidence: 99%